2021
DOI: 10.1186/s12943-021-01322-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk of four types of RNA modification writers defines tumor microenvironment and pharmacogenomic landscape in colorectal cancer

Abstract: Background The four major RNA adenosine modifications, i.e., m6A, m1A, alternative polyadenylation, and adenosine-to-inosine RNA editing, are mediated mostly by the “writer” enzymes and constitute critical mechanisms of epigenetic regulation in immune response and tumorigenesis. However, the cross-talk and potential roles of these “writers” in the tumor microenvironment (TME), drug sensitivity, and immunotherapy remain unknown. Methods We systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 88 publications
6
134
1
Order By: Relevance
“…TAMs can differentiate into M1 macrophages or M2 macrophages. Clinical research has shown that the poor prognosis of cancer patients significantly correlate with the number of M2 macrophages [45,46]. The correlation between MT1L expression and M2 macrophage surface marker expression in our study suggested that MT1L may be involved in macrophage polarization and partially explains the potential mechanism of poor prognosis in BLCA patients with high expression of MT1L.…”
Section: Discussionsupporting
confidence: 55%
“…TAMs can differentiate into M1 macrophages or M2 macrophages. Clinical research has shown that the poor prognosis of cancer patients significantly correlate with the number of M2 macrophages [45,46]. The correlation between MT1L expression and M2 macrophage surface marker expression in our study suggested that MT1L may be involved in macrophage polarization and partially explains the potential mechanism of poor prognosis in BLCA patients with high expression of MT1L.…”
Section: Discussionsupporting
confidence: 55%
“…For example, by extending related studies 25 27 under the multi-label learning framework. Previously, due to the lack of epi-transcriptome datasets in matched biological conditions, cross-talk of multiple RNA modifications was mainly studied via the expression level of relevant RNA modification enzymes 51 . Although the interactions among different RNA modifications can partially be revealed from enzyme-based analysis, it is important to note that the known enzyme genes have multiple biological functions other than writing or erasing RNA modifications, which may contaminate the results.…”
Section: Discussionmentioning
confidence: 99%
“…Since our observations regarding the cross-talk between RNA modifications in colorectal cancer highlighted their therapeutic liability toward immunotherapy (89), it would be interesting to decipher the existence of a similar complex regulatory network in T cells, and to determine whether other RNA methylations might function as a sort of "gas pedal" or "pace keeper" to control T cell clonal expansion, differentiation, and subsequent effector functions. The identification of a specific RNA epigenetic translational checkpoint will advance our knowledge concerning how different RNA methylations are sequentially coordinated to regulate T cell immunity.…”
Section: Discussionmentioning
confidence: 99%